Taxation in the United States - Mikhalkina, Ekaterina; Izák, Vratislav, 1941-; Blažek, Petr; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2012)
The content of this thesis is the evaluation of the United States' tax system. The paper describes particular taxes, its influence on the government budget and the tax policy in the states. The work includes an international comparison of various tax systems among OECD countries, Japan and the U.S. The first part observes general economic indicators of the U.S. The second part describes the historical development of particular taxes since the U.S. Declaration of Independence. The third part is dedicated to tax legislation, description of main taxes, its structures and concepts where all taxes are divided for the simplicity into direct, indirect, property and others taxes. The next part reflects framework for tax analysis. And the last part of the thesis consists of basic comparison between the United States, Japan and OECD counties. The analysis in the last chapter is applicable for the last decade. The conclusion presents main results of analysis and description performed in the work.
Vedoucí práce: Vratislav Izák
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2012
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2012
Způsob přístupu: Internet
Keywords: zdanění a daňová politika [obor dipl. práce]; diplomové práce; master's theses